Socialist Feminism in the Select Poems of Maya Angelou - Cacas, Zoraida; Saluria, Raymark Anthony (Journal of Interdisciplinary Perspectives, 2024)
Maya Angelou is one of the most inspirational African-American poets, novelists, activists, and feminists, who has also been recognized as a prominent and influential voice in literature. This study aimed to engage in an analytical investigation of socialist feminism in the select poems of Maya Angelou using biographical approach and Johannna Brenner’s socialist feminism perspective. The select poems included Woman Work, Alone, On Working White Liberals, When You Come to Me, When I Think about Myself and Caged Bird. The research method of textual analysis was used in the literary investigation of the select poems. The study revealed that Maya Angelou had a challenging and colorful life. Her range of experiences from childhood to adulthood had influenced how she wrote. Her vision and legacy as mirrored in her works especially in her poetry continue to inspire others to fight for equality of all forms in the society. It was also found out that there are a number of significant factors that aided in the development of her work as a writer and a poet. Her life experiences along with her education recreated the way she saw the world. The socio-cultural environment in Arkansas during her period also contributed to her profound writings. The salient characteristics of socialist feminism of Brenner such as representation of women, images of women at home and in the workplace and role of women in the society are highly evident in her body of work. As a socialist feminist, Brenner yearns to end the exploitation of women at home, in the workplace, and in the community. Since this research found out that Angelou is regarded a socialist feminist, it is recommended to analyze other types of feminism such as eco-feminism, liberal, and radical feminism to explore other salient characteristics of feminism embedded in Angelou’s works.